The Use of Schoology Applications in Learning in terms of Student Learning Motivation (Empirical Study on Sports Education Students, Muhammadiyah University of Surakarta) - Maimunah Nur Anisa; Gatot Jariono (International Journal of Educational Research & Social Sciences, 2021)
The purpose of this study is to find out the use of Schoology application in learning reviewed from the motivation of learning in POR UMS students. The population in this study is students of the Sports Education Study Program of Muhammadiyah University of Surakarta class of 2017-2021. The samples used in this study are as many as 220 students, research instruments consist of observations, questionnaires, and interviews, while research sampling techniques using systematic random sampling with a type of systematic random sampling. Data collection techniques using observations, questionnaires, and interviews while this type of research is descriptive quantitative research by analyzing the data that has been collected and then described. The results of this study showed that the use of Schoology application media in the learning process helped students increase motivation in learning by gaining an average percentage of Schoology application usage by 76.82% of the agreed category, while the percentage of the average learning motivation result was 73.18% of category agreed. So it can be concluded that with the acquisition of significant percentage results between the use of Schoology applications and learning motivation there is an increase in learning motivation in POR UMS students by using Schoology applications in the learning process.